Anti-Inflammatory Effects of Essential Oils of Amomum aromaticum Fruits in Lipopolysaccharide-Stimulated RAW264.7 Cells. (25th May 2020) - Dang, Nguyen Hai; Anh, Le Thi Van; Dat, Nguyen Tien
Abstract : Inflammation is a vital physiologic response of cellular injury, infection, or autoimmune activation. Overproduction of proinflammatory mediators may result in the chronic inflammation that leads to many diseases such as rheumatoid arthritis, asthma, multiple sclerosis, and atherosclerosis. In this study, we assessed for the first time the anti-inflammatory effects of the essential oils of Amomum aromaticum fruits (AAE) in RAW264.7 murine macrophage model. As a result, AAE potently inhibited the production of nitric oxide in LPS-induced RAW264.7 cells with the IC50 value of 0.45 ± 0.11 μ g/ml. AAE also dose-dependently reduced the expression of two proinflammatory proteins iNOS and COX-2 in the stimulated cells. Phytochemical analysis revealed that major compositions of the volatile oils including 1, 8 cineole (48.22%), geranial (9.24%), neral (6.72%), α -pinene (2.43%), and α -terpineol (2.28%) may contribute greatly to the inhibition effects due to their anti-inflammatory properties. The results suggest for the potential uses of AAE in chronic inflammation prevention.